Prognostic value of tumour tissue ANG-1 expression and Ang-1 concentration in patients with non-small-cell lung cancer - Zalewska-Ziob, Marzena; Adamek, Brygida; Kasperczyk, Janusz; Dobija-Kubica, Katarzyna (Polish Journal of Pathology, 2022)
Tumor cells stimulate local angiogenesis, resulting in their further multiplication and spread. Angiogenesis is a multifaceted process in which angiopoietins parti- cipate. Angiopoietin-1 (Ang-1) through its receptor Tie2 stimulates endothelial cell survival and the maintenance of the endothelial barrier. These phenomena can support tumour growth by promoting angiogenesis. On the other hand, overproduction of Ang-1 triggers endothelium stability and can lead to angiogenesis inhibition. Because of the ambiguous role of Ang-1, we decided to determine its clinical significance in patients with resectable NSCLC. In a group of 47 patients, tumours and the adjacent non-cancerous tissues were assessed for ANG-1 mRNA expression (using Q-RT-PCR analysis) and Ang-1 concentration (by enzyme-linked immunosorbent assay) together with clinical parameters and the five-year survival rate. ANG-1 expression and Ang-1 concentration were higher in tumour-free tissue, showing no differences between histological types of NSCLC, clinical stage or grading and seemed not to determine the five-year survival. ANG-1 expression and Ang-1 concentration in tumour and tumour-free tissues in patients with NSCLC seem not to be useful as factors supporting either diagnostics or prognosis.